Critical Analysis of the Interpretation of QS. al-Anfal Verse 67: Contextualization of the Meaning of Rebuke to the Prophet - Rachmat Alfisyahar Wakano; Muhamad Mualim; Jaka Ghianovan (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2025)
The concept of infallibility ('iṣmah) of the prophets is an important pillar of Islamic belief. However, a number of verses in the Qur'an seem to imply that the prophets were reprimanded for their decisions, as in the stories of the prophets Adam, Yunus, and Muhammad SAW, which has sparked debate among scholars about the limits of 'iṣmah. Some scholars argue that prophets remain infallible in all aspects, while others acknowledge the possibility of interpretive errors that are immediately corrected by revelation. This study aims to examine Quranic Surah al-Anfal verse 67 as the primary focus in understanding the relationship between infallibility and divine rebuke. This research uses a qualitative approach based on library research, with two main methods of interpretation: classical and contemporary tafsir approaches, as well as analysis of asbāb al-nuzūl and maqāṣid al-sharī'ah. Thus, this study concludes that reprimands against the Prophet function more as an educational method in conveying the values of Sharia to the ummah. This study contributes to clarifying the theological position of the prophets in classical and modern discourse, emphasizing that revelatory correction of the Prophet's ijtihad is a form of divine education (ta'dīb rabbānī), not a rebuke for Sharia errors. This correction actually serves as a mechanism for confirming infallibility by demonstrating Allah's direct guidance in prophetic decisions. This finding enriches the framework of contextual interpretation while bridging literal and hermeneutic understandings, in order to present a balanced and non-extreme narrative in interpreting prophetic integrity